Postharvest control of Botryosphaeria dothidea-induced pear ring rot by Chrysanthemum indicum essential oil: Composition, efficacy, and mechanistic insights - Bin Wang; Sha-Sha Liu; Jia-Ying Wu; Meng-Ran Yu; Yun-Kai Lv; Jian Wang; Li-Juan Wang; Fei Cao (Postharvest Biology and Technology, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Shimia fortis sp. nov., Isolated from Marine Sediment - Xiao-Yu Dong; Pei-Ran Lin; Xin-Yun Tan; Jia-Qi Li; Zong-Jun Du; Meng-Qi Ye (Current Microbiology, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China - Yi-RAN Huang; Yu-Cheng Wang; Xiao-Xuan Meng; Yu-Tao Xiang (Science Bulletin, 2025)

Potential role of dietary whole grains in Alzheimer's disease: bioactive components, mechanistic insights, and epidemiological evidence - Meng Shen; Xinru Yu; Suyang Wu; Ju Qiu; Ran Wang; Kai Li; Qian Zhang (Trends in Food Science & Technology, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

In situ transglutaminase cross-linking mediated protein-stabilized high internal phase emulsion gels to emulate dorsal adipose tissue: The role of continuous phase networks - Liang Guo; Yu-hang Xue; Yi-ran Zhang; Wen-yan Chen; Yao-siyi Yuan; Shen-shen Tian; Yue-Cheng Meng; Jie Chen (Food Chemistry, 2025)

Whey protein-structured oleogels: Effect of α-lactalbumin addition and ultrasonication treatment on oleogelation - Qiu-Ya Ji; Ran Feng; Yu-Nong Chen; Chao Zhang; Jiao Wu; Meng-Jie Yu; Bao Zhang (Food Chemistry, 2025)

Study on the dissolved inorganic carbon cycling and carbon emission during the wet season across cascade hydropower stations on the Jinsha River, southwestern China - Dan Zhang; Yufei Bao; Jingjie Feng; Yu Xu; Yuchun Wang; Ran Li; Yanliang Du; Zhuo Chen; Shanze Li; Jie Wen; Meng Sun (Gondwana Research, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Thiolated dextrin nanoparticles for curcumin delivery: Stability, in vitro release, and binding mechanism - Bao Zhang; Shen Long; Ran Feng; Meng-Jie Yu; Bao-Cai Xu; Han Tao (Food Chemistry, 2025)

Stabilizing emulsions by ultrasound-treated pea protein isolate - tannic acid complexes: Impact of ultrasonic power and concentration of complexes on emulsion characteristics - Meng-Jie Yu; Ran Feng; Shen Long; Han Tao; Bao Zhang (Food Chemistry, 2025)

Modulating rice digestibility: Mechanisms of ultrasound, oleic acid and moist-heat treatments influence structural, physicochemical and digestive properties - Bao Zhang; Qian Gao; Meng-Jie Yu; Ran Feng; Han Tao (Food Chemistry, 2024)

Novel self-assembled micelles of dual-modified dextrin with pH responsiveness via grafted octenyl succinic anhydride and cysteamine for curcumin delivery - Shen Long; Meng-Jie Yu; Ran Feng; Han Tao; Bao Zhang (Food Chemistry, 2024)

Oleic acid treatment of rice grains reduces the starch digestibility: Formation, binding state and fine structure of starch-lipid complexes - Qian Gao; Ran Feng; Meng-Jie Yu; Han Tao; Bao Zhang (Food Chemistry, 2024)

Mitigating interfacial recombination enabling efficient semitransparent organic photovoltaics - Hailin Yu; Jiayu Wang; Yuanhao Li; Tianyu Liu; Yufei Gong; Cenqi Yan; Qichao Ran; Qun Luo; Zupan Mao; Xin Wei; Lei Meng; Changqi Ma; et al. (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Picea pungens exhibits greatest tolerance to short-time thermal stress compared to Picea abies, and Picea omorika - Fangqun Ouyang; Meng Sun; Xia Cui; Mulualem Tigabu; Hui Zhang; Junyu Deng; Junhui Wang; Yu Wei; Ran He (New Forests, 2024)

Reactive oxygen species (ROS) modulate nitrogen signaling using temporal transcriptome analysis in foxtail millet - Hui-Xin Meng; Yu-Ze Wang; Xin-Li Yao; Xin-Ran Xie; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Molecular Biology, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Nitrogen source affects non-aeration microalgal-bacterial biofilm growth progression and metabolic function during greywater treatment - Jiake Li; Beibei Wu; Meng Xu; Xuan Han; Yinuo Xing; Yu Zhou; Mengyao Ran; Yun Zhou (Bioresource Technology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Characterization and immune functional analysis of two new type I crustins in the oriental river prawn Macrobrachium nipponense - Hongxia Jiang; Shuaishuai Zhang; Xuewei Liu; Yizheng Li; Huanxin Li; Ran Zhang; Yuhua Li; Meng Zhang; Lei Wang; Miao Yu; Zhigang Qiao; Xuejun Li (Aquaculture, 2023)

Stress response mechanism of wastewater biological nitrogen removal systems to environmentally realistic concentrations of tire wear particles: Contribution of leachable additives - Jinyu Ye; Ruotong Cheng; Zhoukai Chen; Chengran Fang; Meng Shi; Ran Yu; Hongchun Qian; Xiangdong Xue (Bioresource Technology, 2023)

Distinct composition patterns of bacterial and fungal communities and biogeochemical cycling genes depend on the vegetation type in arid soil - Junling He; Ran Qi; Shuzhi Wang; Xingxing Duan; Liqi Meng; Shutao Ai; Long Yu; Geoffrey Michael Gadd; Wenjuan Song (Applied Soil Ecology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A compound of paraprobiotic and postbiotic derived from autochthonous microorganisms improved growth performance, epidermal mucus, liver and gut health and gut microbiota of common carp (Cyprinus carpio) - Delong Meng; Qiang Hao; Qingshuang Zhang; Zhe Yu; Shubin Liu; Yalin Yang; Chao Ran; Zhen Zhang; Zhigang Zhou (Aquaculture, 2023)

Selenium Deficiency Leads to Reduced Skeletal Muscle Cell Differentiation by Oxidative Stress in Mice - Bo-wen Bao; Zibo Kang; Yu Zhang; Kan Li; Ran Xu; Meng-yao Guo (Biological Trace Element Research, 2023)

An improved approach to estimate ratoon rice aboveground biomass by integrating UAV-based spectral, textural and structural features - Le Xu; Longfei Zhou; Ran Meng; Feng Zhao; Zhengang Lv; Binyuan Xu; Linglin Zeng; Xing Yu; Shaobing Peng (Precision Agriculture, 2022)

Tracking Neural Stem Cells in vivo: Achievements and Limitations - Chun-Ran Xue; Kan Wang; Meng-Ze Zhang; Ze Wang; Ya-Ying Song; Hao-Jun Yu; Yong Hao; Yang-Tai Guan (Stem Cell Reviews and Reports, 2022)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Zinc Deficiency Aggravation of ROS and Inflammatory Injury Leading to Renal Fibrosis in Mice - Ran Xu; Miao-yu Chen; Wan Liang; Yu Chen; Meng-yao Guo (Biological Trace Element Research, 2021)

Annual 30-m land use/land cover maps of China for 1980–2015 from the integration of AVHRR, MODIS and Landsat data using the BFAST algorithm - Yidi Xu; Le Yu; Dailiang Peng; Jiyao Zhao; Yuqi Cheng; Xiaoxuan Liu; Wei Li; Ran Meng; Xinliang Xu; Peng Gong (Science China Earth Sciences, 2020)

Genome-wide analysis sheds light on the high-altitude adaptation of the buff-throated partridge (Tetraophasis szechenyii) - Chuang Zhou; Jake George James; Yu Xu; Hongmei Tu; Xingcheng He; Qinchao Wen; Megan Price; Nan Yang; Yongjie Wu; Jianghong Ran; Yang Meng; Bisong Yue (Molecular Genetics and Genomics, 2020)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

Procalcitonin levels in patients with positive blood culture, positive body fluid culture, sepsis, and severe sepsis: a cross-sectional study - Ying Yu; Xia-Xi Li; Ling-Xiao Jiang; Meng Du; Zhan-Guo Liu; Zhong-Ran Cen; Hua Wang; Zhen-Hui Guo; Ping Chang (Infectious Diseases, 2016)

Reply to Shaocheng Ji’s discussion on ‘Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process’ by Yang et al. (Contrib. Mineral. Petrol., 2014, 167: 1013) - Jian-Jun Yang; Meng-Xi Huang; Hao-Ran Zhang; Cong Yu (Contributions to Mineralogy and Petrology, 2015)

Effects of Tai Chi on adiponectin and glucose homeostasis in individuals with cardiovascular risk factors - Rei-Yeuh Chang; Malcolm Koo; Meng-Ying Ho; Zi-Zi Lin; Zer-Ran Yu; Yen-Fen Lin; Be-Jen Wang (European Journal of Applied Physiology, 2011)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)